2022
DOI: 10.1093/jxb/erac018
|View full text |Cite
|
Sign up to set email alerts
|

Dual control of MAPK activities by AP2C1 and MKP1 MAPK phosphatases regulates defence responses in Arabidopsis

Abstract: Mitogen-activated protein kinase (MAPK) cascades transmit environmental signals and induce stress and defence responses in plants. These signalling cascades are negatively controlled by specific phosphatases of the type 2C Ser/Thr protein phosphatase (PP2C) and dual-specificity phosphatase (DSP) families that inactivate stress-induced MAPKs; however, the interplay between phosphatases of these different types has remained unknown. Our work reveals that different Arabidopsis MAPK phosphatases, the PP2C-type AP2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 94 publications
(164 reference statements)
1
10
0
Order By: Relevance
“…When MAPKKK is activated by a sensor/receptor it can phosphorylate serine/threonine residues of S/TXXXXXS/T, in which X represents any amino acid, to activate downstream MAPKK, after which MAPKK continues to phosphorylate the conserved threonine and tyrosine residues in the TXY motif downward to activate MAPK [ 3 , 4 , 5 , 6 , 7 , 8 ]. MAPK cascades respond to almost all biological or abiotic stresses [ 9 , 10 , 11 ], such as mechanical damage [ 12 ], high salt [ 13 ], low temperature [ 14 ], drought [ 15 ] and pathogen invasion [ 16 ] and widely participate in the process of plant growth and development [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…When MAPKKK is activated by a sensor/receptor it can phosphorylate serine/threonine residues of S/TXXXXXS/T, in which X represents any amino acid, to activate downstream MAPKK, after which MAPKK continues to phosphorylate the conserved threonine and tyrosine residues in the TXY motif downward to activate MAPK [ 3 , 4 , 5 , 6 , 7 , 8 ]. MAPK cascades respond to almost all biological or abiotic stresses [ 9 , 10 , 11 ], such as mechanical damage [ 12 ], high salt [ 13 ], low temperature [ 14 ], drought [ 15 ] and pathogen invasion [ 16 ] and widely participate in the process of plant growth and development [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, immune signalling must be initiated at a specific time plants grow better when there is a fine balance between immunity and growth (Belkhadir et al, 2014;Lozano-Durán & Zipfel, 2015). plants (Ayatollahi et al, 2022;Couto et al, 2016;Segonzac et al, 2014;Singh et al, 2016;Tischer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…By analysing the ability of all RCAR–PP2C combinations to regulate ABA signalling through transient expression in Arabidopsis protoplasts, it was found that the blocking rate of the ABA response by all class A PP2Cs exceeded 90% (Tischer et al., 2017 ). In the class B family, AP2C1 negatively regulates the wound‐induced MAPK signalling pathway (Ayatollahi et al., 2022 ). Members of the class C protein family are involved in cell development (Song et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The biological implications of these interactions should be demonstrated in vivo . Furthermore, the magnitude and duration of MAP kinase signalling effect depend on their activation by upstream kinases and their inactivation by protein phosphatases ( Schweighofer et al., 2007 ; Bartels et al., 2010 ; Ayatollahi et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%